2020
DOI: 10.1055/s-0039-3403474
|View full text |Cite
|
Sign up to set email alerts
|

Whitening Dentifrices Effect on Enamel with Orthodontic Braces after Simulated Brushing

Abstract: Objective This study aimed to evaluate in vitro the effects of whitening dentifrices on enamel color, the shear bond strength of orthodontic brackets and adhesive remnant index (ARI). Materials and Methods Eighty bovine teeth with brackets were randomly divided into four groups (n = 20): control group (GC)–water, test group 1 (GT1)–Colgate Total 12, test group 2 (GT2)–Curaprox Black Is White, and group test 3 (GT3)–Luminous White. All groups were submitted to brushing, simulating 12 months. The specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 30 publications
3
25
0
5
Order By: Relevance
“…This slight whitening effect may be related to the presence of hydrated silica which has greater ability to remove stains from enamel surface compared with other abrasives (4) . This result is consistent with a recent study reported that the toothpastes containing mechanical abrasive were effective in modifying the color of bovine enamel (23) . However, these results were in disagreement with another study that demonstrated that the traditional abrasive toothpaste was not able to improve the tooth color (13) .…”
Section: Discussionsupporting
confidence: 93%
“…This slight whitening effect may be related to the presence of hydrated silica which has greater ability to remove stains from enamel surface compared with other abrasives (4) . This result is consistent with a recent study reported that the toothpastes containing mechanical abrasive were effective in modifying the color of bovine enamel (23) . However, these results were in disagreement with another study that demonstrated that the traditional abrasive toothpaste was not able to improve the tooth color (13) .…”
Section: Discussionsupporting
confidence: 93%
“…They were flattened by means of a metallographic polishing machine PL VO60 (Biopdi, São Carlos, SP, Brazil) to standardize the surfaces. The sample calculation was performed based on the effect sizes found in the literature 14,15 and ISO/TS 11405 16 recommendations for this study design. The sample size of 60 teeth, 20 in each group, provided 80% test power (β=0.20) to detect large effects (f=0.41) for shear bond strength and w=0.48 for ARI, with a significance level of 5% (α=0.05).…”
Section: Orthodontic Bracket Bonding and Area Of Analysismentioning
confidence: 99%
“…The vestibular surface of each test specimen was polished with silicon carbide water paper abrasive discs used consecutively, grit size of 180, 400 and 600 (3M do Brasil Ltda., Sumaré, SP, Brazil), in order to expose the same enamel area for bracket bond 3,[14][15][16] . The flattest portion of the vestibular surface of each crown was maintained as parallel as possible, without exposing the dentin, fixed in orthophthalic resin (Equifibras, Salvador, BA, Brazil), polishing and placed in an ultrasonic bath L-200 (Schuster TM Ltda) for 10 minutes to remove possible polishing residues.…”
Section: Orthodontic Bracket Bonding and Area Of Analysismentioning
confidence: 99%
See 2 more Smart Citations